Maternal Complications during Pregnancy and Risk Factors for Stunting - Rifzul Maulina; Mochammad B. Qomaruddin; Budi Prasetyo; Rachmah Indawati (Wolters Kluwer Medknow Publications, 2024)
Background: Stunting can be prevented by early detection when the mother is pregnant. Early detection can be carried out by looking for risk factors of stunting during pregnancy so that interventions can be early detected. This study aims to assess complications during pregnancy (disease and infection) and risk factors associated with stunting. Materials and Methods: The type of research was observational analytic with a case-control design on 450 mothers who were selected with simple random sampling (150 mothers who have stunting babies aged 0-2 months and 300 mothers who have not stunting babies aged 0-2 months in Malang Regency, Indonesia. This study used secondary data by looking at medical records, namely, laboratory examinations in the mother's book and cohort records at the public health center. This study was conducted from December 2021 to August 2022. Bivariate analysis with Chi-square and multivariate logistic regression was carried out to determine the variables that most influenced the incidence of stunting. Results: The results of multivariate analysis with logistic regression of maternal complications during pregnancy, which are a risk as a factor causing stunting, are Sexually Transmitted Infections (STIs) (Odds Ratio [OR]: 6.36; 95% Confidence Interval [CI]: 2.97-13.62), coronavirus disease 2019 (COVID-19) accompanied by pneumonia (OR: 5.12; 95% CI: 1.87-14.052), human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) (OR: 4.63; 95% CI: 1.10-19.59), hepatitis B (OR: 3.97; 95% CI: 1.253-12.565), pre-eclampsia (OR: 3.88; 95% CI: 1.81-8.30), and heart disease (OR: 3.373; 95% CI: 0.99-11.40). Conclusions: After recognizing the maternal factors that cause stunting, intervention should immediately be carried out on pregnant women with diseases (pre-eclampsia and heart disease) and infections (STI, COVID-19 + pneumonia, HIV/AIDS, and hepatitis B) to prevent stunting early.